2001
DOI: 10.1021/bi010328k
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Changes in the Streptomyces lividans TipAL Protein Imply an Alternative Mechanism of Transcriptional Activation for MerR-Like Proteins

Abstract: TipAL is a Streptomyces transcriptional activator assigned to the MerR/SoxR family based both on homology within its putative DNA recognition domain and the fact that its operator binding sites lie within a region of its promoter normally occupied by RNA polymerase. The tipA gene is also independently translated as the C-terminal ligand-binding domain of TipAL (TipAS; residues 111-254). Both TipAS and TipAL share broad recognition specificity for cyclic thiopeptide antibiotics. The molecular mechanism by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…Antibiotic binding to TipAL increases the affinity to its operator site and stabilizes binding of the RNA polymerase to the ptipA promoter (27). TipAL binds DNA as a dimer and presumably, by analogy to MerR (28,29,34), might activate transcription of tipA by twisting the DNA.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotic binding to TipAL increases the affinity to its operator site and stabilizes binding of the RNA polymerase to the ptipA promoter (27). TipAL binds DNA as a dimer and presumably, by analogy to MerR (28,29,34), might activate transcription of tipA by twisting the DNA.…”
Section: Significancementioning
confidence: 99%
“…As the N-terminal part of TipAS connects to the DNA binding domain in the transcriptional regulator TipAL, its folding upon binding very likely also constitutes the mechanical signal by which antibiotic binding induces expression of tipA and possibly of other MDR genes (24,25). The conformational selection of the unfolded N terminus to a well-defined, almost identical structure in all three TipAS complexes would then position the DNA binding domain in an appropriate way to bind promoter DNA with higher affinity and recruit RNA polymerase to the complex (27). This specific positioning of the DNA binding domain and the subsequent induction of transcription needs to emerge from the specific thiopeptide recognition motif.…”
Section: Nmr Analysis and Structure Determination Of Tipas Antibioticmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-and C-terminal domains are linked together by a long ␣-helix that forms an antiparallel coiled-coil structure that is involved in dimerization ( Fig. 1) (6,7,9,19,21,53).…”
mentioning
confidence: 99%
“…The pTip vectors are tightly regulated expression vectors containing a tipA promoter (P tipA ) (4,14), from which protein expression is induced by the antibiotic reagent thiostrepton (26). In our previous report, we showed that pTip vectors mediate heterologous and homologous protein expression, as they contain multiple cloning sites for 11 restriction enzyme sites and a hexahistidine (six-His) tag sequence and they work over a wide temperature range, from 4 to 35°C.…”
mentioning
confidence: 99%